Sensor Based Irrigation Technology Platform for Sri Lanka - Miller Alexander, R. (University of Jaffna, 2018)
Agriculture can be considered as the most important field for and all living beings. In most of the countries in the world, the staple their population produced through cultivation. There is a new green on the block, the digital green. A rather quiet revolution is happening in the field of agriculture i.e. Agriculture 4.0. Precision Agriculture (PA) is a new concept to Sri Lankan agricultural community. SenzAgro is the first agriculture 4.0 platform in Sri Lanka. The objective of this paper is to identify the methods and implementations that can be applied to the agricultural sector of Sri Lanka. While composing the platform with identified implementations the cost, scientific and technological knowledge of the farmers were taken into consideration.
Keywords: IoT; Irrigation; Sri Lanka; Precision Agriculture